Persistent Fetal Trigeminal Artery with Septopreoptic Holoprosencephaly: Report of an Unusual Association - D., Sunilkumar; K., Nagarajan; M., Kiran; A., Subathra (Journal of Pediatric Neurology, 2020)
Septopreoptic holoprosencephaly (HPE) is a type of HPE characterized by failure of separation of the septal and preoptic regions. Vascular anomalies associated with septopreoptic HPE include twig-like cerebral vessels and azygos anterior cerebral artery, the latter common to all forms of HPE. Here, we describe an 8-year-old boy presenting with developmental delay and abnormal movements who was found to have septopreoptic HPE associated with persistent trigeminal artery in magnetic resonance neuroimaging. This persistence of fetal trigeminal artery in HPE provides a further understanding of the pathogenesis of HPE.
Keywords: persistent trigeminal artery; septopreoptic holoprosencephaly; MRI; developmental delay